PENINGKATAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN MELALUI PENDEKATAN COOPERATIF LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS DI SEKOLAH DASAR - AINI, SUKRA (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study originated from the fact that the school learning undertaken by teachers is conventional, is still centered learning (teaching centered) Civics students study results have not been as expected. Therefore, the researchers in this study used the type of cooperative learning approach Student Teams Achievement Divisions (STAD). This study aims to improve the learning process in class V Civics in the Elementary School District 13 Lubuk Alung Ampek Nagari Agam District. The study was Classroom Action Research (Classroom Action Research). This research uses qualitative and quantitative approaches are implemented in two cycles carried out collaboratively between researchers with teachers. The results after the first cycle demonstrated achievement gained at the meeting I was 69.6% and 76.7% at the second meeting, the study continued on the second cycle was 80.7%. There has been an increase from cycle I to cycle II.   Kata Kunci : pendekatan stad, materi PKn, hasil belajar